2021
DOI: 10.1002/nau.24732
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety of vibegron, a new β3‐adrenoceptor agonist, in older patients with overactive bladder: Post‐hoc analysis of a randomized, placebo‐controlled, double‐blind comparative phase 3 study

Abstract: Aims: To examine the safety and efficacy of vibegron, a new β3-adrenoceptor agonist, in patients aged ≥65 years, with a focus on the effects on cardiovascular system and overactive bladder (OAB) symptoms.Methods: A post-hoc subgroup analysis was performed of a randomized, placebo-controlled, double-blind comparative phase 3 study of vibegron, including those assigned to receive either vibegron 50 mg (V50), vibegron 100 mg (V100), or placebo for 12 weeks. Subjects were stratified into two subgroups based on age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Consequently, the safety analysis of β3 agonists always focuses on possible cardiovascular outcomes including abnormal blood pressure and pulse rate. Thus far, vibegron seems to have minimal impact on cardiovascular parameters [16].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Consequently, the safety analysis of β3 agonists always focuses on possible cardiovascular outcomes including abnormal blood pressure and pulse rate. Thus far, vibegron seems to have minimal impact on cardiovascular parameters [16].…”
Section: Discussionmentioning
confidence: 93%
“…In such context, only one patient in mirabegron had elevated blood pressure and headache in forementioned study [25]. A Japanese post hoc analysis on vibegron 50 mg, 100 mg, or placebo for 12-week demonstrated no cardiovascular AEs including high blood pressure, palpitation, and tachycardia in those with vibegron 50 mg [16]. Future studies with more patients and longer follow-up is warranted.…”
Section: Injmentioning
confidence: 96%
“…8 Additionally, an analysis of a vibegron clinical trial in Japan found no change in blood pressure over the 12-week study period in patients ≥65 years of age. 9 In clinical trials, vibegron also did not increase blood pressure in patients with pre-existing hypertension. In EMPOWUR, no clinically relevant changes from baseline in blood pressure were observed over 12 weeks of vibegron treatment in patients who were or were not hypertensive at baseline.…”
Section: Supporting Informationmentioning
confidence: 99%